Hand In Hand - Aya Qartallo; Raya Ahmad (My University, 2023)
At the beginning of each semester, we notice that there are many publications on university student groups on Facebook, including the presence of some students who are unable to pay tuition fees in whole or in part due to difficult financial conditions, and others who have difficulty in purchasing one of the requirements for their studies, such as a laptop, etc. From here was the birth of the idea of our project. The project aims to help needy students pay their tuition fees, as well as to facilitate donors to find those students. Our application includes many features, including the presence of a personal account for each student from the beneficia ries, in which personal information about the student is stored, specifically the information needed by the Loans and Grants Department for each student, view available scholarships and loans suitable with their qualifications, notify users when a new scholarship or loan is available, promotional ads for hardworking students to urge people to donate for them, contracting with companies of interest so that they provide discounts on supplies needed for students or supporting several stu dents, in exchange for posting advertisements for these companies,chatting between users, searching,light/dark theme, and supporting two languages are features in our project. We visited the university’s grants and loans section to help us add more features to the application. In the end, the idea of our project has not been implemented before exactly as we did, but there are some websites for donations only and others for loans.